Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.31111/nsnr/2020.54.2.429
|View full text |Cite
|
Sign up to set email alerts
|

On the Micarea prasina group (Pilocarpaceae) in the Kaliningrad Region

Abstract: Seven species of Micarea prasina group were found during the lichen study in the northern part of the Kaliningrad Region. M. pseudomicrococca is reported for the first time for Russia, 6 other species are new to the Kaliningrad Region. Morphological, anatomical, and chemical features of the species are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…(Kantelinen et al 2021) and two locations in the Kaliningrad region of Russia, on the bark of Picea abies and lignum of Alnus glutinosa (L.) Gaertn. (Konoreva et al 2020). In this study, 12 specimens were found in four different plots, all being windthrows of Picea abies in nearly natural mixed montane forests.…”
Section: Micarea Pseudomicrococca Launis and Myllysmentioning
confidence: 77%
“…(Kantelinen et al 2021) and two locations in the Kaliningrad region of Russia, on the bark of Picea abies and lignum of Alnus glutinosa (L.) Gaertn. (Konoreva et al 2020). In this study, 12 specimens were found in four different plots, all being windthrows of Picea abies in nearly natural mixed montane forests.…”
Section: Micarea Pseudomicrococca Launis and Myllysmentioning
confidence: 77%
“…1), including 117 species of lichens (lichenized fungi) and one species of saprobic non-lichenized fungus (Microcalicium disseminatum). This number is probably slightly higher because the "Micarea prasina" group distinguished in this work (see Launis et al 2019), represented in the world by 32 and in Poland by 12 species (Konoreva et al 2020), probably includes several taxa in the reserve.…”
Section: Resultsmentioning
confidence: 67%